The Use Of Number Concept Vocabulary Card In Teaching English To Young Learners At Sd Negeri Duwet 02 In 2014/2015 Academic Year - Astri Khalimah, Ansella; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
In general this study aims (1) to describe the implementation of number concept in teaching English vocabulary in SDN Duwet 02 describing (a) the objective, (b) the materials and (c) teaching procedures, (2) to describe the students response, (3) to describe the strength and weakness of teaching vocabulary using number concept. The type of this research is descriptive qualitative research. The writer collects the data by observing the teaching learning process, conducting interview with teacher and students, and taking documentation during teaching-learning process.The technique for analyzing data is data reduction, data display, and conclusion. The result of this research shows that: (1) the objective of teaching English vocabulary is to improve the students vocabulary mastery. The textbook used is handout from the teacher. There are three activities in teaching learning process, such as: opening, learning activities, and closing (2) most of the students gave positive responses. Most of them enjoyed the teaching-learning process. They were very interested in the process of learning in every meeting. (3) Using Number Concept Vocabulary Card, the students can easily memorize the number, because they can study with the real object. However, it can be a challenge for shy students. They are not brave to demonstrate the commands with the materials.